2002
DOI: 10.1002/ijc.10770
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cyclooxygenase‐2 and peroxisome proliferator‐activated receptor‐γ and levels of prostaglandin E2 and 15‐deoxy‐Δ12,14‐prostaglandin J2 in human breast cancer and metastasis

Abstract: Cyclooxygenase-2 (COX-2) expression and peroxisome proliferator-activated receptor-␥ (PPAR␥) inactivation are linked to increased risk of human breast cancer. The purpose of our study was to examine the relationship between COX-2 (with the resulting prostaglandins E 2 , PGE 2 ) and PPAR␥ (and its natural endogenous ligand 15-Deoxy-⌬ 12,14 -prostaglandin J 2 , 15d-PGJ 2 ) at various stages during the development of human breast cancer and its progression to metastasis. Human breast tissue specimens were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
53
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 44 publications
5
53
0
1
Order By: Relevance
“…3). Taken together the studies of Badawi and Badr, the current study and those previous reported, 25 it is clear that there is a stepwise decrease of PPAR␥ from normal healthy breast tissues, 38 tumor unaffected breast tissue, primary tumor tissues to metastatic tumor tissues. This reduction is linked to the prognosis of the patients with breast cancer.…”
Section: Reduced Level Of Pgc-1 In Patients Who Have a Poor Prognosissupporting
confidence: 86%
See 1 more Smart Citation
“…3). Taken together the studies of Badawi and Badr, the current study and those previous reported, 25 it is clear that there is a stepwise decrease of PPAR␥ from normal healthy breast tissues, 38 tumor unaffected breast tissue, primary tumor tissues to metastatic tumor tissues. This reduction is linked to the prognosis of the patients with breast cancer.…”
Section: Reduced Level Of Pgc-1 In Patients Who Have a Poor Prognosissupporting
confidence: 86%
“…Although PGC-1 exhibited similar levels in tumor and normal tissues, the reduction of the co-activator, similar to that of PPAR␥, has clearly occurred in tumors with aggressive nature, i.e., in TNM3 and TNM4 tumors and tumors from patients with a poor prognosis. Badawi and Badr 38 have reported recently that unaffected background normal tissues exhibited lower levels of PPAR␥ than normal breast tissues from non-tumor bearing patients and that metastatic tumors had lower levels of PPAR␥ than the primary tumors. 38 Although the study by Badawi and Badr did not provide information on relationship between PPAR␥ and clinical outcomes, the current study has provided data to show that over a period 6-year follow-up , the levels of PPAR␥ in patients with local recurrence and those who died of breast cancer were significantly lower than those who remained disease free (Fig.…”
Section: Reduced Level Of Pgc-1 In Patients Who Have a Poor Prognosismentioning
confidence: 99%
“…[37][38][39][40] Our results show that HLD downregulates the level of PPARc mRNA. Underexpression of PPARc in rodent and human mammary gland carcinomas 41,42 and in human prostate adenocarcinomas have been reported previously. 43 Moreover, Sarraf et al 44 detected somatic loss-of-function mutations in the gene encoding PPARc in a few cases of sporadic colorectal carcinoma, suggesting that the wild-type gene compromises the survival of abnormal cells.…”
Section: Discussionsupporting
confidence: 65%
“…Thus it has been suggested that high expression of PPARg and low expression of COX-2 in the tumours might be involved in attenuating the capacity of the tumours to develop more malignant nature. Badawi and Badr (2003) described that an increase of COX-2 expression and a decrease of PPARg expression in breast carcinoma tissues were paralleled by increases in the tissue levels of PGE 2 and decreases in 15d-PGJ 2 and their altered expressions might influence the development of human breast carcinoma. COX-2 overexpression has been observed in many tumour types including gynaecological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al (2000) proposed that expression of COX-2 was regulated by a negative feedback loop mediated through PPARg in macrophages. Badawi and Badr (2003) described that the altered expression of COX-2 and PPARg might influence the development of human breast carcinoma and its progression to metastasis. Recently, PPARg has been reported to be localised primarily to granulosa cells in ovarian tissue and to be involved in follicular development (Komar et al, 2001).…”
mentioning
confidence: 99%